A medieval case of digitalis poisoning: the sudden death of Cangrande della Scala, lord of verona (1291–1329). (February 2015) - Fornaciari, Gino; Giuffra, Valentina; Bortolotti, Federica; Gottardo, Rossella; Marvelli, Silvia; Marchesini, Marco; Marinozzi, Silvia; Fornaciari, Antonio; Brocco, Giorgio; Tagliaro, Franco
Abstract: The natural mummy of Cangrande della Scala was exhumed from its tomb in the church of Santa Maria Antiqua in Verona and was submitted to a multidisciplinary study, that included archaeological, palaeopathological, palynological, toxicological and historical investigation. The body of Cangrande, still wearing his precious clothes, was in a good state of preservation. Palynological analyses demonstrated the presence of pollen grains of Digitalis sp./foxglove in the rectum content, along with Matricaria chamomilla /chamomille and Morus nigra /black mulberry. Toxicological analyses showed toxic concentrations of digoxin and digitoxin, two Digitalis glycosides, in the liver and faeces samples. Both palynological and toxicological data suggest an intoxication through the oral administration of an infusion or decoction of leaves and flowers of Digitalis . Cangrande died on July 22 1329, four day after his triumphal entrance in the city of Treviso. The sudden death was preceded by vomit and diarrhoea with fever that, according to written documents, he had contracted a few days before by "drinking from a polluted spring". The gastrointestinal symptoms manifested by Cangrande in his last hours of life are compatible with the early phase of Digitalis intoxication and the hypothesis of poisoning is mentioned by some local historical sources. The palaeopathological analyses confirm a Digitalis poisoning. The most likely hypothesis on the causes of death is that of a deliberate administration of a lethal amount of Digitalis . Although several cases of poisoning through the use of organic substances are known from historical sources, no other direct evidences are documented in the palaeopathological literature. Highlights: The natural mummy of Cangrande della Scala (1291–1329) was examined. Palaeopathological, palynological, toxicological and historical analyses were carried out. Results suggest that Cangrande was victim of Digitalis poisoning. The most likely hypothesis is that of a deliberate administration of a lethal amount of Digitalis .